Glass fiber impregnating compound composition, glass fiber impregnating compound as well as preparation method and application of glass fiber impregnating compound

By using glass fiber wetting agent compositions of sodium dodecyl sulfate, polyvinyl alcohol and color fixing agent G bisammaldehyde resin primary acetate, the problem of poor dispersion effect of glass fiber in gypsum or white water is solved. , achieving uniform dispersion of fibers and improving material properties.

CN119263654AActive Publication Date: 2025-01-07JUSHI GRP CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411387273.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In the prior art, the dispersion effect of glass fiber in gypsum or white water is poor, resulting in the inability to fully and uniformly disperse the fibers, limiting the application field of materials.

Method used

A glass fiber wetting agent composition, including sodium dodecyl sulfate, polyvinyl alcohol and color fixing agent G bisammonaldehyde resin primary condensate acetate as dispersant, and by controlling its proportion and hydrolysis conditions, the positive balance is balanced. Negative charge improves the dispersion effect of fibers.

Benefits of technology

The uniform dispersion of glass fiber in gypsum and glass fiber felt is achieved, which enhances the strength and surface density of the material, and meets the market and application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071218290000091
    Figure BDA0005071218290000091
  • Figure BDA0005071218290000092
    Figure BDA0005071218290000092
  • Figure BDA0005071218290000101
    Figure BDA0005071218290000101
Patent Text Reader

Abstract

The invention provides a glass fiber impregnating compound composition, a glass fiber impregnating compound as well as a preparation method and application of the glass fiber impregnating compound. The glass fiber impregnating compound composition comprises a dispersing agent, a lubricating agent, an antistatic agent and water, the solid content of the glass fiber impregnating compound composition is 0.1-5%, and the glass fiber impregnating compound composition comprises the following components in parts by weight: 0.1-10 parts of a first dispersing agent, 0.1-10 parts of a second dispersing agent, 0.1-10 parts of a third dispersing agent, 0.1-10 parts of the lubricating agent and 0.1-10 parts of the antistatic agent; wherein the first dispersing agent is lauryl sodium sulfate; the second dispersing agent is polyvinyl alcohol; and the third dispersing agent is a color fixing agent G-type bis-ammonia formaldehyde resin initial shrinkage body acetate. According to the glass fiber chopped strand treated by the glass fiber impregnating compound, the reinforced gypsum is relatively high in applicability and good in dispersion effect, and the strength performance of a product is uniform; the dispersing effect in the glass fiber mat is good, and the surface compactness is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass fiber sizing agents, and in particular to a glass fiber sizing agent composition, a glass fiber sizing agent, and a preparation method and application thereof. Background Art

[0002] Adding glass fibers to gypsum can improve the elastic coefficient and flexibility of the wallboard, so that the gypsum is not easily damaged during transportation and processing. At the same time, because glass fibers are inorganic fibers, they are non-flammable and have good chemical resistance, which greatly improves the safety of use and can also greatly extend the service life of gypsum materials. At present, glass fiber reinforced gypsum materials have been widely used in the field of building materials, the most common of which are gypsum boards and gypsum wallboards. Glass fiber felt is used for epoxy-covered copper plates and electrical insulation products. It has the characteristics of high heat resistance, good thermal insulation performance, high sound absorption rate, high exhaust gas purification efficiency, corrosion resistance, insect resistance, mildew resistance, low absorption rate, good vibration resistance, flame retardancy, light weight, etc. Glass fiber felt is mainly used as the base material of roof waterproofing materials.

[0003] Modified asphalt anti-wood coil has the characteristics of corrosion resistance, high strength, good anti-wood property, good dimensional stability, high porosity, and easy to be impregnated with asphalt. By adding reinforcing yarns over the entire width of the glass fiber mat, the longitudinal strength and tear resistance of the glass fiber mat can be improved. With the in-depth development of the material industry, the application requirements of glass fiber reinforced gypsum composite materials and glass fiber mats are constantly increasing, and the limitations of the material characteristics themselves are becoming more and more obvious.

[0004] As a reinforcing material, ordinary glass fiber surface treatment agents can disperse glass fibers to a certain extent in gypsum slurry or white water, but cannot achieve a single-filament dispersion effect, resulting in the inability to fully and evenly disperse glass fibers in gypsum. For glass fiber mats, the inability to fully disperse glass fibers will lead to glass fiber bundles, uneven gaps, or uneven weight of the mat surface. This greatly limits the application of glass fibers in fields such as gypsum and glass fiber mats. Therefore, it is very important to develop a high-dispersion sizing agent for chopped glass fiber strands to improve the dispersion effect of glass fibers in gypsum or white water, in order to further expand the application field of such materials. Summary of the invention

[0005] The main purpose of the present invention is to provide a glass fiber sizing composition, a glass fiber sizing and a preparation method and application thereof, so as to solve the problem of poor dispersion effect of glass fiber in gypsum or white water in the prior art.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a glass fiber sizing composition is provided, comprising a dispersant, a lubricant, an antistatic agent and water, wherein the solid content of the glass fiber sizing composition is 0.1% to 5%, and the glass fiber sizing composition comprises, by weight, 0.1 to 10 parts of a first dispersant, 0.1 to 10 parts of a second dispersant, 0.1 to 10 parts of a third dispersant, 0.1 to 10 parts of a lubricant and 0.1 to 10 parts of an antistatic agent; wherein the first dispersant is sodium lauryl sulfate; the second dispersant is polyvinyl alcohol; and the third dispersant is a color fixing agent, namely, G-type bis(amino formaldehyde) resin primary condensate acetate.

[0007] Furthermore, in parts by weight, the glass fiber sizing composition comprises 0.3 to 8 parts of a first dispersant, 0.3 to 8 parts of a second dispersant, 0.3 to 8 parts of a third dispersant, 0.3 to 8 parts of a lubricant and 0.3 to 8 parts of an antistatic agent; preferably, the glass fiber sizing composition comprises 0.5 to 6 parts of a first dispersant, 0.5 to 6 parts of a second dispersant, 0.5 to 6 parts of a third dispersant, 0.5 to 6 parts of a lubricant and 0.5 to 6 parts of an antistatic agent; further, preferably, the glass fiber sizing composition comprises 0.6 to 5 parts of a first dispersant, 0.6 to 5 parts of a second dispersant, 0.6 to 5 parts of a third dispersant, 0.6 to 4 parts of a lubricant and 0.5 to 4 parts of an antistatic agent.

[0008] Furthermore, the mass ratio of the first dispersant, the second dispersant and the third dispersant is 1-3:1-3:1-3.

[0009] Furthermore, the relative molecular mass of the polyvinyl alcohol is 6000-30000; and / or the relative molecular mass of the fixing agent type G bis(amino formaldehyde) resin primary condensate acetate is 150-300.

[0010] Furthermore, the lubricant is polyethylene glycol, and the relative molecular mass of the polyethylene glycol is 100 to 10,000, preferably 200 to 6,000, and further preferably 400 to 2,000.

[0011] Furthermore, the antistatic agent is a water-soluble quaternary ammonium salt, and the water-soluble quaternary ammonium salt is selected from any one or more of polydodecyl dimethyl benzyl ammonium chloride solution, tetradecyl dimethyl benzyl ammonium chloride solution, tetrabutyl ammonium hydroxide solution and hexadecyl dimethyl benzyl ammonium chloride solution.

[0012] According to another aspect of the present invention, a glass fiber sizing is provided, which is prepared by mixing a sizing composition, wherein the sizing composition is the aforementioned glass fiber sizing composition, wherein the pH value of the glass fiber sizing is 4-10, preferably 5-7.

[0013] According to another aspect of the present invention, there is provided a method for preparing a glass fiber sizing, the method comprising: step S1, hydrolyzing a raw material comprising a first dispersant, a second dispersant, a third dispersant and water to obtain a first mixture; step S2, diluting and mixing a raw material comprising a lubricant, an antistatic agent and water to obtain a second mixture; step S3, stirring and mixing the first mixture and the second mixture to obtain the glass fiber sizing, wherein the above step S1 comprises: performing a first hydrolysis of the second dispersant with water to obtain a first hydrolysis product; performing a second hydrolysis of the first dispersant with water to obtain a second hydrolysis product, and mixing the first hydrolysis product with the second hydrolysis product to obtain an intermediate hydrolysis product; performing a third hydrolysis of the third dispersant with water to obtain a third hydrolysis product, and mixing the third hydrolysis product with the intermediate hydrolysis product to obtain the first mixture; wherein the temperatures of the first hydrolysis, the second hydrolysis and the third hydrolysis are each independently 80-90°C, and / or the times of the first hydrolysis, the second hydrolysis and the third hydrolysis are each independently 10-20 minutes.

[0014] Furthermore, the above-mentioned step S2 includes: using water to perform a first dilution treatment and a second dilution treatment on the lubricant and the antistatic agent respectively to obtain a lubricant liquid and an antistatic agent liquid; and / or, the temperature of the first dilution treatment and the second dilution treatment is independently 20 to 30°C, and / or, the time of the first dilution treatment and the second dilution treatment is independently 10 to 20 minutes; and / or step S3 includes: mixing the first mixture with the lubricant liquid and the antistatic agent liquid in turn to obtain a glass fiber impregnation agent.

[0015] According to yet another aspect of the present invention, there is provided a glass fiber produced by coating the glass fiber sizing agent.

[0016] According to another aspect of the present invention, there is provided a use of the above-mentioned glass fiber impregnating agent in gypsum.

[0017] By applying the technical solution of the present invention, the dispersant, as the main component of the glass fiber sizing agent, not only plays an important role in the uniform dispersion of the fibers, but also has a decisive influence on the strength of the glass fiber reinforced gypsum and the quality of the glass fiber felt surface. The above three different types of dispersants are used in this application, among which sodium dodecyl sulfate is an anionic dispersant with a negative charge. The color fixer G type diamino formaldehyde resin primary condensate acetate is a cationic dispersant with a positive charge. Polyvinyl alcohol is a non-ionic dispersant with no charge. By controlling the type and content of the above dispersants, the positive and negative charges in the glass fiber sizing agent are balanced, thereby improving the dispersing effect of the glass fiber sizing agent. At the same time, the non-ionic polyvinyl alcohol can simultaneously improve the dispersing effect and buffering effect of the glass fiber sizing agent. If its proportion is too low, it will lead to local charge imbalance of the glass fiber sizing agent. Therefore, the content of the above three preferred dispersants helps to improve the synergistic effect between them, so that the glass fiber sizing agent achieves the best dispersibility. On the one hand, the glass fiber chopped strands treated with the above glass fiber sizing agent have strong applicability for reinforcing gypsum, good dispersion effect, and uniform strength performance of the product. On the other hand, the glass fiber chopped strands treated with the sizing agent of the present invention have good dispersion effect in the glass fiber mat, no glass fiber bundles on the mat surface, good surface density, and meet market and application needs. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0019] As analyzed in the background technology of this application, the prior art has the problem that the dispersion effect of glass fiber in gypsum or white water is poor. In order to solve the above problem, this application provides a glass fiber wetting agent composition, a glass fiber wetting agent and a preparation method and application thereof.

[0020] In a typical embodiment of the present application, a glass fiber sizing composition is provided, comprising a dispersant, a lubricant, an antistatic agent and water, wherein the solid content of the glass fiber sizing composition is 0.1% to 5%, and the glass fiber sizing composition comprises, by weight: 0.1 to 10 parts of a first dispersant, 0.1 to 10 parts of a second dispersant, 0.1 to 10 parts of a third dispersant, 0.1 to 10 parts of a lubricant and 0.1 to 10 parts of an antistatic agent; wherein the first dispersant is sodium dodecyl sulfate; the second dispersant is polyvinyl alcohol; and the third dispersant is a color fixing agent, namely, G-type diamino formaldehyde resin primary condensate acetate.

[0021] Dispersant, as the main component of glass fiber sizing agent, not only plays an important role in the uniform dispersion of fibers, but also plays a decisive role in the strength of glass fiber reinforced gypsum and the quality of glass fiber felt surface. The above three different types of dispersants are used in this application, among which sodium dodecyl sulfate is an anionic dispersant with a negative charge. The color fixer G type diamino formaldehyde resin primary condensate acetate is a cationic dispersant with a positive charge. Polyvinyl alcohol is a non-ionic dispersant with no charge. By controlling the type and content of the above dispersants, the positive and negative charges in the glass fiber sizing agent are balanced, thereby improving the dispersing effect of the glass fiber sizing agent. At the same time, non-ionic polyvinyl alcohol can simultaneously improve the dispersing effect and buffering effect of the glass fiber sizing agent. If its proportion is too low, it will lead to local charge imbalance of the glass fiber sizing agent. Therefore, the content of the above three preferred dispersants helps to improve the synergistic effect between them, so that the glass fiber sizing agent achieves the best dispersibility. On the one hand, the glass fiber chopped strands treated with the above glass fiber sizing agent have strong applicability for reinforcing gypsum, good dispersion effect, and uniform strength performance of the product. On the other hand, the glass fiber chopped strands treated with the sizing agent of the present invention have good dispersion effect in the glass fiber mat, no glass fiber bundles on the mat surface, good surface density, and meet market and application needs.

[0022] In one embodiment of the present application, the glass fiber sizing composition comprises, by weight: 0.3-8 parts of a first dispersant, 0.3-8 parts of a second dispersant, 0.3-8 parts of a third dispersant, 0.3-8 parts of a lubricant and 0.3-8 parts of an antistatic agent; preferably, the glass fiber sizing composition comprises: 0.5-6 parts of a first dispersant, 0.5-6 parts of a second dispersant, 0.5-6 parts of a third dispersant, 0.5-6 parts of a lubricant and 0.5-6 parts of an antistatic agent; further, preferably, the glass fiber sizing composition comprises: 0.6-5 parts of a first dispersant, 0.6-5 parts of a second dispersant, 0.6-5 parts of a third dispersant, 0.6-4 parts of a lubricant and 0.5-4 parts of an antistatic agent.

[0023] It is preferred to control the weight fraction of each component in the glass fiber sizing composition within the above range, which is conducive to promoting the active functional groups of each dispersant to form a very smooth mold on the surface of the glass fiber in an aqueous solution environment, thereby greatly reducing the bonding force between the glass fibers, thereby exerting the dispersion effect of the glass fibers in the aqueous solution state, and achieving the effect of fiber filamentization; at the same time, it can also take into account the protectiveness of the glass fibers, thereby improving the dispersion performance of the glass fibers in subsequent processing.

[0024] In one embodiment of the present application, the mass ratio of the first dispersant, the second dispersant and the third dispersant is 1-3:1-3:1-3.

[0025] By controlling the mass ratio of the first dispersant, the second dispersant and the third dispersant within the above range, it is more conducive to promoting the balance of positive and negative charges in the glass fiber impregnant, thereby improving the dispersion effect of the glass fiber in gypsum or white water, and further achieving the monofilamentization effect of the glass fiber.

[0026] In one embodiment of the present application, the relative molecular mass of the polyvinyl alcohol is 6000-30000; and / or the relative molecular mass of the fixing agent type G bis(amino formaldehyde) resin primary condensate acetate is 150-300.

[0027] By controlling the molecular weights of polyvinyl alcohol and the color fixing agent G-type bis(amino formaldehyde) resin primary condensate acetate within the above ranges, it is beneficial to improve the dispersion effect of the glass fiber in the aqueous solution state and to promote the stability of the entire dispersion system.

[0028] In one embodiment of the present application, the lubricant is polyethylene glycol, and the relative molecular mass of the polyethylene glycol is 100 to 10,000, preferably 200 to 6,000, and further preferably 400 to 2,000.

[0029] The preferred lubricant in the present application is polyethylene glycol, and controlling the relative molecular weight of polyethylene glycol within the above range helps to reduce the amount of wear on the surface of the glass fiber during production and processing, thereby improving the smoothness of the use of the glass fiber.

[0030] In one embodiment of the present application, the antistatic agent is a water-soluble quaternary ammonium salt, and the water-soluble quaternary ammonium salt is selected from any one or more of polydodecyl dimethyl benzyl ammonium chloride solution, tetradecyl dimethyl benzyl ammonium chloride solution, tetrabutyl ammonium hydroxide solution and hexadecyl dimethyl benzyl ammonium chloride solution.

[0031] The antistatic agent in the present application is a water-soluble quaternary ammonium salt, and the above types of antistatic agents are preferred to reduce the risk of poor dispersibility due to agglomeration of glass fibers during processing, thereby helping the glass fibers to continue to maintain a good dispersion effect after being dispersed into single fibers.

[0032] In another typical embodiment of the present application, a glass fiber sizing is provided, which is prepared by mixing a sizing composition, wherein the sizing composition is the aforementioned glass fiber sizing composition, wherein the pH value of the glass fiber sizing is 4-10, preferably 5-7.

[0033] The glass fiber sizing obtained from the above sizing composition of the present application has excellent dispersibility. It is preferred to control the pH value of the glass fiber sizing within the above range, which is conducive to promoting the uniform dispersion of the components of the dispersant glass fiber sizing composition, thereby avoiding precipitation or stratification caused by improper pH value, and thus ensuring the uniformity and stability of the glass fiber sizing as a whole.

[0034] In another typical embodiment of the present application, a method for preparing a glass fiber sizing is provided, the method comprising: step S1, hydrolyzing a raw material including a first dispersant, a second dispersant, a third dispersant and water to obtain a first mixture; step S2, diluting and mixing a raw material including a lubricant, an antistatic agent and water to obtain a second mixture; step S3, stirring and mixing the first mixture and the second mixture to obtain a glass fiber sizing. Wherein, the above step S1 comprises: using water to perform a first hydrolysis on the second dispersant to obtain a first hydrolysis product; using water to perform a second hydrolysis on the first dispersant to obtain a second hydrolysis product, and mixing the first hydrolysis product with the second hydrolysis product to obtain an intermediate hydrolysis product; using water to perform a third hydrolysis on the third dispersant to obtain a third hydrolysis product, and mixing the third hydrolysis product with the intermediate hydrolysis product to obtain a first mixture; wherein the temperature of the first hydrolysis, the second hydrolysis and the third hydrolysis is independently 80-90°C, and / or the time of the first hydrolysis, the second hydrolysis and the third hydrolysis is independently 10-20 minutes.

[0035] In the present application, the above step-by-step mixing method is helpful to promote more complete mixing of the components in the glass fiber sizing, thereby helping to improve the dispersion effect and efficiency of the components in the glass fiber sizing composition. Among them, the preferred hydrolysis conditions and hydrolysis order above are helpful to improve the efficiency and effect of the hydrolysis of the first dispersant, the second dispersant and the third dispersant in water, thereby helping to promote more complete mixing of the components in the glass fiber sizing.

[0036] In one embodiment of the present application, the above-mentioned step S2 includes: using water to perform a first dilution treatment and a second dilution treatment on the lubricant and the antistatic agent respectively to obtain a lubricant liquid and an antistatic agent liquid; and / or, the temperature of the first dilution treatment and the second dilution treatment is independently 20 to 30°C, and / or, the time of the first dilution treatment and the second dilution treatment is independently 10 to 20 minutes; and / or step S3 includes: mixing the first mixture with the lubricant liquid and the antistatic agent liquid in turn to obtain a glass fiber impregnation agent.

[0037] The above preferred dilution conditions help to improve the efficiency and effect of diluting the lubricant and antistatic agent in water. The diluted lubricant and antistatic agent are easier to mix evenly with other components in the glass fiber sizing, reducing precipitation or stratification, which is more conducive to evenly coating the glass fiber sizing on the surface of the glass fiber, thereby improving the dispersion effect of the glass fiber in the aqueous solution state.

[0038] In another typical embodiment of the present application, a glass fiber produced by coating with the above-mentioned glass fiber sizing agent is provided.

[0039] The glass fiber chopped strands treated with the impregnating agent of the present invention can enhance the applicability of gypsum materials and glass fiber felt, and can be processed and used smoothly. The glass fiber has an excellent dispersion effect in the white water dispersion of gypsum slurry or glass fiber felt, and can meet the needs of these two major markets and applications at the same time.

[0040] In another typical embodiment of the present application, there is provided an application of the above-mentioned glass fiber impregnating agent in gypsum.

[0041] Applying the above-mentioned glass fiber impregnating agent to gypsum helps to enhance the applicability of gypsum materials and glass fiber felt, facilitates processing and use, and has an excellent dispersion effect of glass fiber in gypsum slurry.

[0042] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0043] The raw materials of each component in the glass fiber sizing composition used in Examples 1 to 17 of the present invention are as follows:

[0044] The first dispersant uses sodium lauryl sulfate;

[0045] The second dispersant uses polyvinyl alcohol;

[0046] The third dispersant uses the color fixer G type bis(amino formaldehyde) resin primary condensate acetate (manufacturer: Hangzhou Electrochemical Group Auxiliary Chemical Co., Ltd., model: color fixer G);

[0047] Polyethylene glycol was used as lubricant;

[0048] The quaternary ammonium salt antistatic agent is a tetrabutylammonium hydroxide solution, and its mass concentration is about 10wt%.

[0049] The method for obtaining the glass fiber sizing agent from the above glass fiber sizing agent composition is specifically as follows:

[0050] In a clean container, add sodium dodecyl sulfate that has been hydrolyzed for 10 minutes with 5-10 times 80℃ deionized water, then add polyvinyl alcohol that has been hydrolyzed for 10 minutes with 10 times 80℃ deionized water, then add color fixer G type diamino formaldehyde resin primary condensate acetate that has been hydrolyzed for 10 minutes with 10 times 80℃ deionized water, then add polyethylene glycol diluted with 5 times room temperature deionized water, then add antistatic agent diluted and dissolved with 20 times room temperature deionized water, finally add room temperature deionized water to replenish the weight of the wetting agent to the set value, stir well for 30 minutes and set aside.

[0051] Table 1 below shows the specific formulas of Examples 1 to 12, and the values ​​of the wetting agent components are all weight percentages of each component.

[0052] Embodiment 13

[0053] The difference from Example 10 is that the mass ratio of the first dispersant, the second dispersant and the third dispersant is 1:2:1, and the glass fiber sizing is finally obtained.

[0054] Embodiment 14

[0055] The difference from Example 10 is that the mass ratio of the first dispersant, the second dispersant and the third dispersant is 1:4:1, and the glass fiber sizing is finally obtained.

[0056] Embodiment 15

[0057] The difference from Example 10 is that the first dispersant uses sodium lauryl sulfate, 0.7 parts;

[0058] The second dispersant uses polyvinyl alcohol, 0.7 parts;

[0059] The third dispersant is the color fixative G type bis(amino formaldehyde) resin primary condensate acetate, 0.7 parts;

[0060] The lubricant is methyl silicone oil, molecular weight 210, 0.7 parts;

[0061] The antistatic agent is tetrabutylammonium hydroxide solution, with a mass concentration of about 10wt%, 0.7 parts, and finally a glass fiber sizing agent is obtained.

[0062] Example 16

[0063] The difference from Example 10 is that the first dispersant uses sodium lauryl sulfate, 0.7 parts;

[0064] The second dispersant uses polyvinyl alcohol, 0.7 parts;

[0065] The third dispersant is the color fixative G type bis(amino formaldehyde) resin primary condensate acetate, 0.7 parts;

[0066] The lubricant is pentaerythritol, molecular weight 136, 0.7 parts:

[0067] The antistatic agent is tetrabutylammonium hydroxide solution, with a mass concentration of about 10wt%, 0.7 parts, and finally a glass fiber sizing agent is obtained.

[0068] Embodiment 17

[0069] The difference from Example 10 is that the first dispersant uses sodium lauryl sulfate, 0.7 parts;

[0070] The second dispersant uses polyvinyl alcohol, 0.7 parts;

[0071] The third dispersant is the color fixative G type bis(amino formaldehyde) resin primary condensate acetate, 0.7 parts;

[0072] The lubricant is magnesium dodecyl sulfate, molecular weight 555, 0.7 parts;

[0073] The antistatic agent is tetrabutylammonium hydroxide solution, with a mass concentration of about 10wt%, 0.7 parts, and finally a glass fiber sizing agent is obtained.

[0074] In order to further demonstrate the beneficial effects of the present invention, the performance of the sizing agent for wet-process chopped strands of glass fiber for gypsum and wet-process glass fiber mat according to the embodiment of the present invention was compared with the sizing agents of different formula combinations, and the specific results are shown in Table 2. The formulas of the sizing agents in each comparative example are as follows:

[0075] Comparative Example 1

[0076] The difference from Example 10 is that the first dispersant uses polyacrylic acid sodium salt, 0.7 parts;

[0077] Use polyacrylate, 0.7 parts;

[0078] The second dispersant uses polyvinyl alcohol, 0.7 parts;

[0079] The third dispersant is the color fixative G type bis(amino formaldehyde) resin primary condensate acetate, 0.7 parts;

[0080] The lubricant is polyethylene glycol with a molecular weight of 1000, 0.7 parts;

[0081] The antistatic agent is tetrabutylammonium hydroxide solution, with a mass concentration of about 10wt%, 0.7 parts, and finally a glass fiber sizing agent is obtained.

[0082] Comparative Example 2

[0083] The difference from Example 10 is that the first dispersant uses sodium lauryl sulfate, 0.7 parts;

[0084] The second dispersant uses polyvinyl alcohol, 0.7 parts;

[0085] The third dispersant uses trimethyloctadecyl ammonium bromide, 0.7 parts;

[0086] Lubricant: polyethylene glycol, molecular weight 1000, 0.7 parts;

[0087] The antistatic agent, tetrabutylammonium hydroxide solution, has a mass concentration of about 10wt%, 0.7 parts, and finally obtains the glass fiber sizing agent.

[0088] Comparative Example 3

[0089] The difference from Example 10 is that the first dispersant uses sodium lauryl sulfate, 0.7 parts;

[0090] The second dispersant uses polyvinyl alcohol, 0.7 parts;

[0091] The lubricant is polyethylene glycol, molecular weight 200, 0.7 parts;

[0092] The antistatic agent is tetrabutylammonium hydroxide solution, with a mass concentration of about 10wt%, 0.7 parts, and finally a glass fiber sizing agent is obtained.

[0093] Comparative Example 4

[0094] The difference from Example 10 is that the first dispersant uses polyvinyl alcohol, 0.7 parts;

[0095] The second dispersant is the color fixative G type bis(amino formaldehyde) resin primary condensate acetate, 0.7 parts;

[0096] The lubricant is polyethylene glycol, molecular weight 200, 0.7 parts;

[0097] The antistatic agent is tetrabutylammonium hydroxide solution, with a mass concentration of about 10wt%, 0.7 parts, and finally a glass fiber sizing agent is obtained.

[0098] The performance test results of Comparative Examples 1 to 4 are shown in Table 2.

[0099] Performance Test:

[0100] The combustible content of the glass fiber of the present invention (i.e., the ratio of the amount of the impregnating agent coated on the glass fiber to the mass of the glass fiber) is generally controlled to be 0.01-0.50%. The specific value needs to be based on the performance of the raw material itself. From the performance indicators that the product needs to achieve and the experimental test results, the product produced with a combustible content of 0.01-0.20% can meet the requirements for dispersibility and reinforcement.

[0101] The specific test results of the chopped strands produced according to a certain glass fiber production process are shown in Table 1.

[0102] In Table 1 below, chopped strands are added to the wet-process thin mat dispersant "white water", and the mixture is mixed at a ratio of 7:10000 with reference to the Q / JS J6651 standard, and then stirred by a mixer to obtain a monofilament glass fiber solution, and then the solution is passed through a circular filter with a diameter of 26 cm to remove the dispersant "white water", thereby obtaining monofilament dispersed glass fibers, and then the filter is placed in a 105°C oven for 2 hours, and the dried glass fiber mat is separated from the filter to obtain the prepared wet-process glass fiber mat, which is cut into 5cm*15cm tensile specimens (for testing tensile strength), and the combustible content of the glass fiber, the moisture content of the glass fiber, the tensile breaking strength and the dispersibility of the glass fiber mat are compared according to the test standards in Table 1.

[0103] The tensile breaking strength is tested according to GB / T 6006.2-2013 standard. The larger the value, the higher the tensile strength.

[0104] The dispersion is tested according to Q / JS J6651 standard. The smaller the value, the better the dispersion.

[0105] Table 1

[0106]

[0107] Table 1

[0108]

[0109]

[0110] Table 2

[0111]

[0112] As can be seen from the above table, by comparing the corresponding test results in Examples 1 to 17 with the test results in Comparative Examples 1 to 4, we found that the dispersant ratio and the type of lubricant have a direct impact on the dispersion effect and the tensile strength at break.

[0113] As the ratio of dispersant to lubricant in Examples 1 to 6 decreases, the dispersibility is improved, but when the ratio reaches that of Example 7, the dispersion effect is not improved much;

[0114] At the same time, according to Examples 7 and 8, after the proportion of the antistatic agent decreases, the dispersibility will be further improved, and the tensile strength will increase;

[0115] In Examples 9 to 11, as the ratio of the dispersant, lubricant and antistatic agent reaches a certain range, especially the three dispersants need to be used in a ratio of 1:1:1, the dispersibility and tensile strength both reach relatively excellent values.

[0116] Based on the above samples, we can obtain a satisfactory sizing agent formula by improving the dispersibility. In particular, the wet-process glass fiber mat material reinforced by the glass fiber prepared in Example 10 has the characteristics of high tensile strength and good dispersibility in white water, and its comprehensive performance is higher than that of other comparative examples.

[0117] Examples 15 to 17 differ from Example 10 only in the type of lubricant, and the tensile strength at break of Examples 15 to 17 is lower than that of Example 10, indicating that the type of lubricant has a direct effect on the tensile strength at break.

[0118] Comparative Examples 1, 2 and Example 10 all use three dispersants, but the types of dispersants are different. The dispersibility of Comparative Examples 1 and 2 is far inferior to that of Example 10, indicating that the type of dispersant has a direct impact on the dispersibility.

[0119] Comparative Examples 3 and 4 not only have different types of dispersants from Example 10, but also use only two dispersants. Their dispersion effects are far inferior to those of Example 10, indicating that the use of three dispersants in proportion has a direct impact on dispersibility and tensile strength.

[0120] In summary, the glass fiber roving treated with the sizing agent described in the present invention has strong applicability as a reinforced wet-process glass fiber felt material, is smooth to process and use, has excellent product performance, outstanding dispersion performance, and meets market and application requirements.

[0121] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0122] Dispersant, as the main component of glass fiber sizing agent, not only plays an important role in the uniform dispersion of fibers, but also plays a decisive role in the strength of glass fiber reinforced gypsum and the quality of glass fiber felt surface. The above three different types of dispersants are used in this application, among which sodium dodecyl sulfate is an anionic dispersant with a negative charge. The color fixer G type diamino formaldehyde resin primary condensate acetate is a cationic dispersant with a positive charge. Polyvinyl alcohol is a non-ionic dispersant with no charge. By controlling the type and content of the above dispersants, the positive and negative charges in the glass fiber sizing agent are balanced, thereby improving the dispersing effect of the glass fiber sizing agent. At the same time, non-ionic polyvinyl alcohol can simultaneously improve the dispersing effect and buffering effect of the glass fiber sizing agent. If its proportion is too low, it will lead to local charge imbalance of the glass fiber sizing agent. Therefore, the content of the above three preferred dispersants helps to improve the synergistic effect between them, so that the glass fiber sizing agent achieves the best dispersibility. On the one hand, the glass fiber chopped strands treated with the above glass fiber sizing agent have strong applicability for reinforcing gypsum, good dispersion effect, and uniform strength performance of the product. On the other hand, the glass fiber chopped strands treated with the sizing agent of the present invention have good dispersion effect in the glass fiber mat, no glass fiber bundles on the mat surface, good surface density, and meet market and application needs.

[0123] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A glass fiber sizing composition, comprising a dispersant, a lubricant, an antistatic agent and water, wherein the solid content of the glass fiber sizing composition is 0.1% to 5%, characterized in that: In parts by weight, the glass fiber sizing composition comprises: 0.1 to 10 parts of a first dispersant; 0.1 to 10 parts of a second dispersant; 0.1 to 10 parts of a third dispersant; 0.1 to 10 parts of the lubricant; 0.1 to 10 parts of the antistatic agent; Among them, the first dispersant is sodium dodecyl sulfate; the second dispersant is polyvinyl alcohol; and the third dispersant is the color fixing agent type G bis(amino formaldehyde) resin primary condensate acetate.

2. The glass fiber sizing composition according to claim 1, characterized in that: In parts by weight, the glass fiber sizing composition comprises: 0.3 to 8 parts of the first dispersant; 0.3 to 8 parts of the second dispersant; 0.3 to 8 parts of the third dispersant; 0.3 to 8 parts of the lubricant; 0.3 to 8 parts of the antistatic agent; Preferably, the glass fiber sizing composition comprises: 0.5 to 6 parts of the first dispersant; 0.5 to 6 parts of the second dispersant; 0.5 to 6 parts of the third dispersant; 0.5 to 6 parts of the lubricant; 0.5 to 6 parts of the antistatic agent; Furthermore, it is preferred that the glass fiber sizing composition comprises: 0.6 to 5 parts of the first dispersant; 0.6 to 5 parts of the second dispersant; 0.6 to 5 parts of the third dispersant; 0.6 to 4 parts of the lubricant; 0.5 to 4 parts of the antistatic agent.

3. The glass fiber sizing composition according to claim 1 or 2, characterized in that: The mass ratio of the first dispersant, the second dispersant and the third dispersant is 1-3:1-3:1-3.

4. The glass fiber sizing composition according to any one of claims 1 to 3, characterized in that: The relative molecular mass of the polyvinyl alcohol is 6000-30000; and / or the relative molecular mass of the color fixing agent type G bis(amino formaldehyde) resin primary condensate acetate is 150-300.

5. The glass fiber sizing composition according to any one of claims 1 to 4, characterized in that: The lubricant is polyethylene glycol, and the relative molecular mass of the polyethylene glycol is 100-10000, preferably 200-6000, and further preferably 400-2000.

6. The glass fiber sizing composition according to any one of claims 1 to 5, characterized in that: The antistatic agent is a water-soluble quaternary ammonium salt, and the water-soluble quaternary ammonium salt is selected from any one or more of polydodecyl dimethyl benzyl ammonium chloride solution, tetradecyl dimethyl benzyl ammonium chloride solution, tetrabutyl ammonium hydroxide solution and hexadecyl dimethyl benzyl ammonium chloride solution.

7. A glass fiber sizing agent prepared by mixing a sizing agent composition, characterized in that: The sizing composition is the glass fiber sizing composition according to any one of claims 1 to 6, wherein the pH value of the glass fiber sizing is 4-10, preferably 5-7.

8. A method for preparing the glass fiber sizing according to claim 7, characterized in that: The preparation method comprises: Step S1, hydrolyzing a raw material including a first dispersant, a second dispersant, a third dispersant and water to obtain a first mixture; Step S2, diluting and mixing the raw materials including the lubricant, the antistatic agent and water to obtain a second mixture; Step S3, stirring and mixing the first mixture and the second mixture to obtain a glass fiber sizing; Wherein, the step S1 comprises: Using water to perform a first hydrolysis on the second dispersant to obtain a first hydrolysis product; Performing a second hydrolysis on the first dispersant with water to obtain a second hydrolyzate, and mixing the first hydrolyzate with the second hydrolyzate to obtain an intermediate hydrolyzate; Performing a third hydrolysis on the third dispersant with water to obtain a third hydrolysis product, and mixing the third hydrolysis product with the intermediate hydrolysis product to obtain the first mixture; The temperatures of the first hydrolysis, the second hydrolysis and the third hydrolysis are each independently 80 to 90° C., and / or the times of the first hydrolysis, the second hydrolysis and the third hydrolysis are each independently 10 to 20 minutes.

9. A glass fiber produced by coating with the glass fiber sizing according to claim 7.

10. Use of the glass fiber sizing agent according to claim 7 in gypsum.

Citation Information

Patent Citations

  • Binder for glass chopped strand mats

    CN101925638A

  • Glass fiber impregnating compound for automobile roof dedicated yarns

    CN109320101A

  • Method for growing plants

    CN115943129A

  • Treated glass fibers for use in an aqueous dispersion to manufacture nonwoven mat

    EP0104555A2

  • Silver halide photographic material and method of forming radiation image using said material

    US5460916A